2017
DOI: 10.1016/j.eurpsy.2017.01.2023
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Mental Disorders in the Eastern Mediterranean Region, 1990–2013

Abstract: The eastern Mediterranean region (EMR) is witnessing an increase in mental illness. With ongoing unrest, this is expected to rise. This is the first study to quantify the burden of mental disorders in the EMR. We used data from the global burden of disease study (GBD) 2013. DALYs (disability-adjusted life years) allow assessment of both premature mortality (years of life lost–YLLs) and nonfatal outcomes (years lived with disability–YLDs). DALYs are computed by adding YLLs and YLDs for each age-sex-country grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…According to the 2001 World Health 10-20% of children and adolescents globally suffer from a mental disorder and 50% of mental disorders start before 14 years of age. 3 Mental disorders are also a leading contributor to the global disease burden: in 2013, 5.4% of global DALYs (Disability-Adjusted Life Years) and 17.4% of global YLDs (Years Lived with Disability) were due to mental disorders. About 90% of suicides are due to underlying mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2001 World Health 10-20% of children and adolescents globally suffer from a mental disorder and 50% of mental disorders start before 14 years of age. 3 Mental disorders are also a leading contributor to the global disease burden: in 2013, 5.4% of global DALYs (Disability-Adjusted Life Years) and 17.4% of global YLDs (Years Lived with Disability) were due to mental disorders. About 90% of suicides are due to underlying mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to decreased life expectancy due to associated medical conditions, such as diabetes, heart diseases and stroke, respiratory conditions, and suicide [3,4] The World Health Organization reported that more than half of mental disorders starts to manifest during adolescence, and globally one in ve adolescents suffers a form of disabling mental disorder, and when they are not taken in consideration, this could result in lifelong adverse consequences, in addition to decrease in compliance with health regimens, and impaired productivity and safety of societies [4]. A systematic review of data from the Eastern Mediterranean Region, showed a raise of more than 10% for the total burden of mental disorders over the past two decades, which outstand the burden in other regions around the globe, including developing regions such as sub-Saharan Africa [5]. Additionally, the review revealed a wide range of the 12-month prevalence of mental illnesses and psychological distresses, between 11.0% and 40.1%, and 15.6% and 35.5%, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mental health disorder is one of the most common health conditions, and the largest single source of economic burden globally, with depression constituting the leading cause of the disease burden. 1–3 Over the past years, there have been widespread commitments to enhance the provision of mental health services. 2,4–6 In Lebanon, efforts to integrate mental health into primary healthcare were initiated via the 2015–2020 National Mental Health Strategy developed by the Ministry of Public Health (MoPH).…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Over the past years, there have been widespread commitments to enhance the provision of mental health services. 2,4–6 In Lebanon, efforts to integrate mental health into primary healthcare were initiated via the 2015–2020 National Mental Health Strategy developed by the Ministry of Public Health (MoPH). One of the main objectives of the strategy is to improve the detection, assessment, and management of depression in primary care settings.…”
Section: Introductionmentioning
confidence: 99%